Rationale for the clinical use of adipose-derived mesenchymal stem cells for COVID-19 patients - Rogers, Christopher J.; Harman, Robert J.; Bunnell, Bruce A.; Schreiber, Martin A.; Xiang, Charlie; Wang, Fu-Sheng; Santidrian, Antonio F.; Minev, Boris R. (Journal of translational medicine, 2020)
In late 2019, a novel coronavirus (SARS-CoV-2) emerged in Wuhan, capital city of Hubei province in China. Cases of SARS-CoV-2 infection quickly grew by several thousand per day. Less than 100 days later, the World Health Organization declared that the rapidly spreading viral outbreak had become a global pandemic. Coronavirus disease 2019 (COVID-19) is typically associated with fever and respiratory symptoms. It often progresses to severe respiratory distress and multi-organ failure which carry a high mortality rate. Older patients or those with medical comorbidities are at greater risk for severe disease. Inflammation, pulmonary edema and an over-reactive immune response can lead to hypoxia, respiratory distress and lung damage. Mesenchymal stromal/stem cells (MSCs) possess potent and broad-ranging immunomodulatory activities. Multiple in vivo studies in animal models and ex vivo human lung models have demonstrated the MSC’s impressive capacity to inhibit lung damage, reduce inflammation, dampen immune responses and aid with alveolar fluid clearance. Additionally, MSCs produce molecules that are antimicrobial and reduce pain. Upon administration by the intravenous route, the cells travel directly to the lungs where the majority are sequestered, a great benefit for the treatment of pulmonary disease. The in vivo safety of local and intravenous administration of MSCs has been demonstrated in multiple human clinical trials, including studies of acute respiratory distress syndrome (ARDS). Recently, the application of MSCs in the context of ongoing COVID-19 disease and other viral respiratory illnesses has demonstrated reduced patient mortality and, in some cases, improved long-term pulmonary function. Adipose-derived stem cells (ASC), an abundant type of MSC, are proposed as a therapeutic option for the treatment of COVID-19 in order to reduce morbidity and mortality. Additionally, when proven to be safe and effective, ASC treatments may reduce the demand on critical hospital resources. The ongoing COVID-19 outbreak has resulted in significant healthcare and socioeconomic burdens across the globe. There is a desperate need for safe and effective treatments. Cellular based therapies hold great promise for the treatment of COVID-19. This literature summary reviews the scientific rationale and need for clinical studies of adipose-derived stem cells and other types of mesenchymal stem cells in the treatment of patients who suffer with COVID-19.